Metodologi Penelitian Keagamaan: Dekonstruksi Hermeneutik I - Fariz Pari (Faculty of Ushuluddin Syarif Hidayatullah State Islamic University, 2006)
The main issue of this writing is the methodology for religious research, meaning this study is a methodological research. Methodological studies fall within the realm of the philosophy of science. In the context of scientific research, there are several key terms that are interrelated and have similarities, namely methodology, method, and theory. Therefore, in the context of this research, it is necessary to first explain the differences in meaning and the relationship between methodology, method, and theory.